LINGUOCULTURAL CHARACTERISTICS OF NICKNAMES FORMED AS A RESULT OF PROFESSIONALISMS - Manzura Karimboyeva Dilmuratovna (International Journal of Literature and Language Studies, 2026)
This article examines the linguocultural characteristics of nicknames formed on the basis of professions, occupations, official positions, and titles in the Uzbek language, particularly in the Khorezm dialects. The study analyzes the semantic, functional, and cultural features of occupationally motivated nicknames and their role in reflecting the social life, traditional crafts, and historical realities of the local population. Special attention is paid to the processes through which professional designations transform into anthroponymic units and become stable markers of individuals, families, and even entire lineages. The research demonstrates that such nicknames serve not only as means of personal identification and differentiation but also as carriers of cultural memory, preserving information about traditional occupations, social structures, and linguistic peculiarities. The article further explores the relationship between professional nicknames and the linguistic worldview of the Khorezm people, highlighting their significance as valuable sources for onomastic, ethnolinguistic, and linguocultural studies.